Redes dialógicas com educandos de uma escola estadual do Espírito Santo sobre o novo ensino médio: o que dizem os estudantes? - Graciliano, Vitor Martins (2024)
The central theme of this study is the composition of dialogic networks with students about the New High School (NMS). Its general objective is to set up dialogical networks with a group of students enrolled in a state school in Espírito Santo in order to understand the enunciations about the NEM in their formative processes. To this end, the specific objectives are: a) to understand the process of creating and implementing the New Secondary Education and the main guidelines that guide this policy in Brazilian education and in the Espírito Santo State Education Network, i.e. history, legal foundations and pedagogical guidelines; b) to problematize the operationalization of the New High School in the daily life of a teaching unit of the Espírito Santo State Education Network and seek to understand, through dialogical networks set up with a group of students, their understanding of the policy in question; c) to prepare, as an educational product, a notebook with the systematization of the round table discussions held with the students. As a theoretical reference, it dialogues with Paulo Freire and authors who deal with NEM. The methodology is based on qualitative and participatory research, carried out through document consultation, moments of participant observation and conversation circles with students in the third year of secondary school at a state school in Espírito Santo. As a result, the students indicated that: a) the New High School is far from meeting the needs/expectations of the working class; b) the suppression of subjects has had an incisive and negative impact on the processes of appropriation of knowledge; c) the lack of teacher training to work with the new policy favors decontextualized teaching practices; d) there are power relations within schools that disempower dialogue between students and educators; e) the aforementioned policy was designed to scrap the social right to Education for students coming from the working class. In addition, the young people say they want to continue studying, including the desire to go on to higher education, and that there is a need to re-evaluate this policy, so that it is thought of from multiple perspectives and strengthens the social right to education, as prescribed by the 1988 Federal Constitution and Law No. 9.394/96 on the Guidelines and Bases of National Education.